2021
DOI: 10.1002/aesr.202170032
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Magnesium Transport in Spinel Chalcogenides

Abstract: In the area of sustainable energy storage, batteries based on multivalent ions such as magnesium have been attracting considerable attention due to their potential for high energy densities. Furthermore, they are typically also more abundant than, e.g., lithium. However, as a challenge their low ion mobility in electrode materials remains.This study addresses the ionic conductivity in spinel host materials which represent a promising class of cathode and solid-electrolyte materials in Mg-ion batteries. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Among these compounds, MgSc 2 Se 4 has emerged as a promising contender with a remarkably low migration barrier of E a = 0.37 eV. [ 2,31–33 ] Nevertheless, its suitability as a solid electrolyte is impeded by a significant partial electronic conductivity. Moreover, studies have indicated that the mobility of magnesium in chalcogenide spinels that include lanthanoids escalates proportionally with the lanthanoid's size.…”
Section: Materials Classesmentioning
confidence: 99%
See 4 more Smart Citations
“…Among these compounds, MgSc 2 Se 4 has emerged as a promising contender with a remarkably low migration barrier of E a = 0.37 eV. [ 2,31–33 ] Nevertheless, its suitability as a solid electrolyte is impeded by a significant partial electronic conductivity. Moreover, studies have indicated that the mobility of magnesium in chalcogenide spinels that include lanthanoids escalates proportionally with the lanthanoid's size.…”
Section: Materials Classesmentioning
confidence: 99%
“…Ternary materials such as inorganic oxides, [ 26,27 ] hydrides, [ 28–30 ] and chalcogenides [ 2,25,31–33 ] display commendable bulk ionic conductivities. Among these, chalcogenide spinel lattices have been recognized as ionic conductors with high ion mobility, [ 31,33 ] a crucial property for solid electrolytes.…”
Section: Fundamental Mechanisms Of Ion Mobilitymentioning
confidence: 99%
See 3 more Smart Citations